A taxonomic study of Chinese Empoascini (Hemiptera: Cicadellidae: Typhlocybinae) (III) - Qin, Dao-Zheng; Liu, Yang; Zhang, Ya-Lin (Zootaxa, 2011)
Four genera of Chinese Empoascini (Hemiptera: Cicadellidae: Typhlocybinae) are reviewed. Two of these, Goifa Dworakowska 1977 and Ifugoa Dworakowska & Pawar 1974, are reported for the first time from China. Three genera, Homa Distant 1908, Goifa Dworakowska 1977 and Schizandrasca Anufriev 1972, are redescribed and the differences between each genus and related genera are discussed. Homa sinensis Qin & Zhang, sp. n. from Yunnan Province (S.W. China) is described and illustrated; one new combination, Goifa tangailensis (Ahmed & Samad, 1972) n. comb. (from Paolia Lower), is proposed and one new synonym is created, i.e. Goifa aprocessa Mann & Sohi, 1993 is a junior synonym of Goifa tangailensis (Ahmed & Samad, 1972).